2017
DOI: 10.1057/s41262-017-0033-9
|View full text |Cite
|
Sign up to set email alerts
|

Consumer–brand identification revisited: An integrative framework of brand identification, customer satisfaction, and price image and their role for brand loyalty and word of mouth

Abstract: Citation:Popp, B. and Woratschek, H. service/product brands. The results demonstrate that identification, satisfaction, and price image significantly influence both loyalty and word of mouth. Moreover, we find significant interrelationships among the constructs: identification positively influences both satisfaction and price image, which also increases satisfaction. By disclosing the relative importance of three separate ways of gaining and retaining customers, this study helps managers more appropriately cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 97 publications
7
77
0
8
Order By: Relevance
“…Interpersonal communication skills are strongly influenced by social media [74,75]. Thus, the Electronic word of mouth (eWOM) is a kind of information exchange between receiver and sender using electronic and digital media [76,77].…”
Section: Electronic Word Of Mouth (Ewom) As a Mediatormentioning
confidence: 99%
“…Interpersonal communication skills are strongly influenced by social media [74,75]. Thus, the Electronic word of mouth (eWOM) is a kind of information exchange between receiver and sender using electronic and digital media [76,77].…”
Section: Electronic Word Of Mouth (Ewom) As a Mediatormentioning
confidence: 99%
“…The brand of a product represents certain values, provides added value, and gives a distinct identity to the product, causing a consumer to be willing to pay a premium price for that product [32]. The consumer perception of a brand guides consumer purchasing behavior [33]. It also offers "a sign of quality" [34] (p. 226).…”
Section: Attitudes About the Brand Of Products With Environmentally Fmentioning
confidence: 99%
“…In his research of the moderating role of consumer-brand identification on consumer responses to purchase regret, Davvetas (2017) concluded that regret decreases consumer satisfaction level and increases brand-switching intentions. Studies indicate that regret is most directly related to brand switching behavior (Popp and Woratschek, 2017). In a similar vein, the present study seeks to examine whether regret in stock out conditions causes brand switching or brand disloyalty.…”
Section: Regret and Consumer Brand Loyaltymentioning
confidence: 93%